Riding the waves of social commerce: an empirical study of Malaysian entrepreneurs - Noor Azuan Hashim,; Shifa Mohd Nor,; Hawati Janor, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The emergence of social media has made it possible for a person with internet connection to communicate with thousands of other people. Because of the heavy usage of social media there is substantial interest in making this medium a commercial site, particularly among entrepreneurs who want to explore the potential of their businesses. Any entrepreneur can experience various benefits and effects from advertising their products and services on social media, including an increase in the number of fans and advertisement views and/or an increase in sales and return on investment as social media channel product and business information to targeted customers at a minimal cost. However, there are limited studies on social media, particularly how it affects business interaction, which formed the focus of this study. Face-to-face surveys were conducted involving 105 Malaysian entrepreneurs who had access to social media. The findings revealed that most entrepreneurs in this study believed that social commerce is the future way of doing their businesses. In fact, they believed that every entrepreneur needs to engage with social media as they would not only allow the entrepreneur to discuss his products and services with other people but also assist him to make vital and critical business decisions.